2011
DOI: 10.1002/jhm.1001
|View full text |Cite
|
Sign up to set email alerts
|

Learning needs of physician assistants working in hospital medicine

Abstract: BACKGROUND: Hospital Medicine is growing rapidly, and the number of physician assistants (PAs) in this field is expected to grow. However, there is no available data related to the learning needs of PA hospitalists. OBJECTIVE: To conduct a needs assessment for PA hospitalists who may be embarking on a hospitalist career. DESIGN: Cross‐sectional survey based on the Core Competencies in Hospital Medicine. SETTING/PARTICIPANTS: A sample of hospitalist PAs working in the United States. MEASUREMENTS: Amount of expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…28 To this point, in one survey of hospitalist PAs, almost all reported that they would have been interested in completing a fellowship, even it meant a lower initial salary. 29 Despite having the same general goals and using similar national resources, our study reveals that APP fellows are trained and assessed very differently between programs. This might represent an area of future growth in the field of hospitalist APP education.…”
Section: Discussionmentioning
confidence: 84%
“…28 To this point, in one survey of hospitalist PAs, almost all reported that they would have been interested in completing a fellowship, even it meant a lower initial salary. 29 Despite having the same general goals and using similar national resources, our study reveals that APP fellows are trained and assessed very differently between programs. This might represent an area of future growth in the field of hospitalist APP education.…”
Section: Discussionmentioning
confidence: 84%
“…Studies have shown that APPs are interested in formal postgraduate hospital medicine training, even if it means having a lower stipend during the first year after graduating from their NP or PA program. 9,15,18 The growing need for hospitalists, driven by residency workhour reform, increased age and complexity of patients, and the need to improve the quality of inpatient care while simultaneously reducing waste, has contributed to the increasing utilization of and need for highly qualified APPs in hospital medicine. 11,19,20 We established a fellowship to train APPs.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalists need to be attuned to the liability risks related to the care of patients requiring surgical management and ensure areas of responsibility are clearly delineated between the hospital medicine and surgical services 26 . We also found that hospitalist claims increasingly involve PAs and NPs, likely reflecting their increasing role in providing care on hospitalist services 27,28 . The naming of these other services and provider types does not necessarily mean a breakdown in interdisciplinary collaboration occurred.…”
Section: Discussionmentioning
confidence: 79%
“…26 We also found that hospitalist claims increasingly involve PAs and NPs, likely reflecting their increasing role in providing care on hospitalist services. 27,28 The naming of these other services and provider types does not necessarily mean a breakdown in interdisciplinary collaboration occurred. Rather, these findings highlight the importance of including these surgical services, PAs, and NPs as integral participants in the patient safety and risk management efforts undertaken by hospitalists.…”
Section: Discussionmentioning
confidence: 99%